Lembaga Mediasi Perbankan sebagai Alternatif Penyelesaian Sengketa Perbankan di Indonesia - Zulfi Diane Zaini (KEADILAN PROGRESIF, 2012)
Peculiarly relation which intertwin among bank with its him relied on trust principle, however in its him oftentimes cannot be obviated by the existence of dispute between client with bank side. The mentioned in general early with the happening of raised by complain is client side to bank because feel getting disadvantage by finansial. Indonesia Bank (BI) as banking authority in Indonesia have big enough share to overcome all kind of problems of arising out at any times, specially problems related to banking operational activity namely denunciatings of bank client. In its growth at the moment so much banking products which on the market to all client, what later by signifikan also affect at often arise problems in consequence of expanding assorted him of banking product. For that Indonesia Bank have to always cope to increase protection of client, what oftentimes seen in his, that client side accept to treat is unjust the than bank side.